The Effect of Digital Transformation on SMEs using O2O Platforms : Focusing on Customer Engagement - Shin, Kayoung; Jeong, Jaeyeon; Jang, Moonkyoung (Asia Pacific Journal of Information Systems, 2022)
The purpose of this study is to investigates the effect of SMEs’ digital transformation efforts in O2O platforms on customer engagement. This study focuses on digitalization, which is a practically viable phase for SMEs using O2O platforms among the three digital transformation stages (digitization, digitalization, and digital transformation). This study specifically categorizes digital transformation efforts into three categories: information diversity, responsiveness to customers, and the degree of functional use. To analyze the impact of these efforts on customer engagement, we conducted a zero-inflated negative binomial regression using the dataset provided by Naver SmartPlace, a representative O2O platform in South Korea. The results present that the positive relationship between these aforementioned factors and customer engagement. Thus, this study demonstrates that utilizing O2O platforms can be an effective strategy for SMEs that lack the resources to achieve a successful digital transformation.